2010
DOI: 10.1007/s00011-010-0265-6
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of TLR7 prior to polymicrobial sepsis improves the immune control of the inflammatory response in adult mice

Abstract: TLR7 seems to be essential for pathogen defence not only in viral but also in bacterial infections. Pharmacological stimulation of this receptor prior to induction of sepsis improves the host's capacity to cope with pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Similar findings were also reported with other innate immune receptors, where genetic deficiency of TLR2 or MyD88 confers beneficial effect against polymicrobial sepsis 40,41 . On the other hand, Koerner et al 42 reported that stimulation of TLR7 before the colon ascendens stent peritonitis improved the immune control of the inflammatory response in the mice. Mice treated with R848 (TLR7 ligand) before sepsis induction exhibited a reduction of proinflammatory cytokine in the spleen and alleviated bacterial loading in the peritoneum/ spleen as well as decreased thymus and spleen apoptosis, indicating a trend of improvement even though no mortality data was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were also reported with other innate immune receptors, where genetic deficiency of TLR2 or MyD88 confers beneficial effect against polymicrobial sepsis 40,41 . On the other hand, Koerner et al 42 reported that stimulation of TLR7 before the colon ascendens stent peritonitis improved the immune control of the inflammatory response in the mice. Mice treated with R848 (TLR7 ligand) before sepsis induction exhibited a reduction of proinflammatory cytokine in the spleen and alleviated bacterial loading in the peritoneum/ spleen as well as decreased thymus and spleen apoptosis, indicating a trend of improvement even though no mortality data was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are almost no data available on that subject. In one report, intravenous injection of R-848 prior to sepsis induction using the colon ascendens stent peritonitis model increased cytokine release and bacterial clearance, but the effect on survival was not reported ( 152 ). Finally, considering that excessive TLR activation induced by viruses or bacteria may have detrimental effects for the host, it might be of interest to generate TLR7/8 antagonists to counteract overwhelming immune activation in conditions of severe infections.…”
Section: Toll-like Receptor 7 Andmentioning
confidence: 99%
“…In addition, mice deficient in TLR9, a receptor for unmethylated CpG motifs present in bacterial DNA, were resistant to lethal polymicrobial sepsis and have improved the survival rate [ 16 ]. TLR7, regarded as a receptor for viral RNA, pharmacological activation of it prior to induction of sepsis, improved the host's capacity to cope with pathogens [ 17 ]. MyD88, serving as one of the key adaptors for all TLRs signaling pathways, except TLR3 which transduces its signal through TRIF.…”
Section: Discussionmentioning
confidence: 99%